Understanding blast-induced neurotrauma: how far have we come?. (8th June 2017) - Cernak, Ibolja
Blast injuries, including blast-induced neurotrauma (BINT), are caused by blast waves generated during an explosion. Accordingly, their history coincides with that of explosives. Hence, it is intriguing that, after more than 1000 years of using explosives, our understanding of the pathological consequences of blast and body/brain interactions is extremely limited. Postconflict recovery mechanisms seemingly include the suppression of painful experiences, such as explosive injuries. Unfortunately, ignoring the knowledge generated by previous generations of scientists retards research progress, leading to superfluous and repetitive studies. This article summarizes clinical and experimental findings published about blast injuries and BINT following the wars of the 20th and 21th centuries. Moreover, it offers a personal view on potential factors interfering with the progress of BINT research working toward providing better diagnosis, treatment and rehabilitation for military personnel affected by blast exposure.